On the value of combining surface and cross‐borehole ERT measurements to study artificial tile drainage processes. Issue 6 (1st May 2014) - Clément, R.; Moreau, S.; Henine, H.; Guérin, A.; Chaumont, C.; Tournebize, J.
Abstract : Many articles have shown the usefulness of electrical resistivity tomography (ERT) where characterizing spatial electrical resistivity variations over time associated with water content variations. In a case study of artificial drainage processes in comparison to isolated measurements of the temporal variation in water content, ERT could be used to obtain additional qualitative spatial information (2D or 3D). Indeed, there have been no articles relating the advantages of using ERT to study tile drainage processes. The aim of this article is to explore the effectiveness of the ERT method for delineating soil moisture spatial patterns, following their temporal variations in the context of artificial drainage. First, in the numerical description, taking into account the current knowledge on artificial drainage processes, the authors evaluate the combination of surface and cross‐borehole ERT measurements and different array types. In a field application, the surface and cross‐borehole combination helps to obtain better information on the soil structure and to optimize electrical resistivity monitoring during tile drainage processes. In the second part of the article, the comparison between the ERT data sets and ancillary data from TDR sensors provides a useful critical evaluation of ERT for studying water transfer in waterlogged soil influenced by artificial drainage. The field results showed that ERT contributes additional 2D information on resistivity as related to the water content, which complements single TDR measurements.